Optimization of the TEGs Configuration (Series/Parallel) in Energy Harvesting Systems with Low-Voltage Thermoelectric Generators Connected to Ultra-Low Voltage DC-DC Converters - Morais, Flavio [UNESP]; Carvalhaes-Dias, Pedro; Duarte, Luis; Spengler, Anderson; Paiva, Kleber de; Martins, Thiago; Cabot, Andreu; Dias, Jose Siqueira (Mdpi, 2020)
Solar radiation and human activity generate ubiquitous temperature gradients that could be harvested by thermoelectric generators (TEGs). However, most of these temperature gradients are in the range of very few degrees and, while TEGs are able to harvest them, the resulting output voltages are extremely small (a few hundreds of mV), and DC-DC converters are necessary to boost them to usable levels. Impedance matching between TEGs and DC-DC converter plays a fundamental role in the energy harvesting efficiency. Therefore, it is essential to determine the output power of the system in different configurations, in order to decide on the optimum TEG connection. Here, we present an electronic circuit to measure the maximum power that can be harvested with low-voltage TEGs connected to a DC-DC converter. The developed circuit is an electronic controlled load that drains the maximum current from the output of the DC-DC converter while maintaining its output voltage at the maximum allowed value. Using a mechanical set-up able to apply precise low temperature gradients between the hot and cold side of the TEGs, experimental data using different configurations of TEGs are obtained. The measured results show that, for ultra-low voltages, the TEG ensemble's output impedance plays an important role not only in the amount of the energy scavenged, but also in the onset temperature of the energy harvesting.
Keywords: energy harvesting; thermoelectric generators; energy measurement; series and parallel TEGs ensemble; ultra-low voltage DC-DC converters